The Influence of Social Media on Tourist Expectations in Yogyakarta : Indonesia - Syafira Ayu Salsabilla; Ahmad Hudaiby Galih Kusumah (Jurnal Ilmiah Hospitality Management, 2026)
Social media has become an important source of tourism information through user-generated content (UGC). This study aims to examine the influence of social media usage intensity on motives for accepting UGC and its effects on trust in UGC and tourists’ emotional expectations toward Yogyakarta. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results show that social media usage intensity significantly influences motives for accepting UGC. Furthermore, motives for accepting UGC positively affect trust in UGC and tourists’ emotional expectations. These findings indicate that active social media use encourages the acceptance of UGC, which strengthens trust in tourism information and shapes positive emotional expectations toward a destination. This study contributes to understanding the role of UGC in shaping tourists’ emotional expectations toward tourism destinations.